Circulation Development of Bayuangga Bus Terminal, Probolinggo City - Syahriza, Aditya Fahmi; Dadoes Soemarwanto; Darmansjah Tjahja Prakasa (Kirana Publisher (KNPub), 2025)
Bayuangga Terminal, the largest Type A passenger terminal in Probolinggo City, has seen a significant rise in passenger and bus traffic. Despite this growth, its circulation system remains inefficient and does not meet Type A terminal standards, hindering infrastructure development. This study focuses on improving transportation connectivity through architectural and spatial analysis of the terminal’s circulation, where irregular intersections between bus and pedestrian corridors pose safety risks. Methods include literature review, field observations, and interviews with the Terminal’s Technical Management Unit (UPT). Results highlight the critical safety issue caused by overlapping bus and passenger lanes. Recommendations involve separating pedestrian and vehicle lanes, redesigning bus routes, and upgrading passenger facilities. These interventions aim to optimize circulation, enhance user safety, and improve operational efficiency. Implementing these measures will help Bayuangga Terminal meet Type A standards and better serve its growing user base.